YciR, a Specific 3′-Phosphodiesterase, Plays a Role in the Pathogenesis of Uropathogenic Escherichia coli CFT073 - Zhang, Si; Wang, Jingting; Fan, Yu; Meng, Wang; Qian, Chengqian; Liu, Peng; Wei, Yi; Yuan, Chao; Du, Yuhui; Yin, Zhiqiu (Frontiers in Microbiology, 2022)
Urinary tract infections (UTIs), with a characteristic of recurrence and resistance to antibiotics due to misuse, remain a common health and economic issue for patients. Uropathogenic Escherichia coli (UPEC), which is capable of evading immune response by forming intracellular bacterial communities (IBCs) in the cytoplasm of bladder epithelial cells (BECs) after the invasion, is proved to be a prevailing cause of UTIs. Cyclic dimeric guanosine monophosphate (c-di-GMP) is a small molecule responsible for eliciting the innate immune response of the host only if it has not been degraded by some phosphodiesterases such as YciR. The relationship between YciR and c-di-GMP level is inconclusive in UPEC. In this study, we investigated the gene expression profile of UPEC in BECs and identified yciR as an up-regulated gene. Western Blot revealed that YciR enhances the virulence of UPEC by inhibiting the phosphorylation of NF-κB. It is also exhibited that the expression of yciR could be repressed by HupB in a directly binding manner. We found YciR, a novel PDE, and defined its possible function in innate immune evasion. We also demonstrated that YciR is a HupB-dependent PDE that degrades c-di-GMP and that a low concentration of c-di-GMP might make NF-κB less phosphorylated, reducing the host's pro-inflammation. This is the first time that YciR has been identified as a virulence factor in the pathogenesis of UPEC. These findings further increase the understanding of the pathogenesis of UPEC and provide a theoretical basis for further studies.